Manajemen Laba Dan Tax Avoidance Terhadap Nilai Perusahaan dimoderasi Kualitas Audit - Cindy O. Pangemanan; Muslichah Muslichah (Jurnal Akuntansi dan Pajak, 2023)
The goal of this study to examine the impact of earnings management and tax avoidance on firm value with audit quality as a moderating variable. Population of this study is infrastructure, transportation, and logistics sectors listed on the IDX from 2017-2021. By using purposive sampling, the sample used in the study was 28 companies, with a period of 5 years, obtained 140 observational data. The results of the study show that earnings management doesn’t affect on firm value, tax avoidance has a positive effect on firm value, and audit quality can’t moderate the relationship among earnings management and firm value. On the other hand, audit quality can weaken the impact of tax avoidance on firm value.